Cuts of meat, preliminary case study in Alagoas (Brazil) with new approach/Cortes de carne, um estudo de caso preliminar em Alagoas (Brasil), com nova abordagem - André Maia Gomes Lages; Jonathan de França Santos; Evelly Vitória Oliveira de Jesus; Fabiano Lucas da Silva; Kennyo Douglas Pedrosa Dias; Vitória Leandra Santos Camilo (Universidade Estadual de Alagoas, 2020)
This work aims to determine the beef cuts and their low prices, dividing the front and back cuts. There are significant differences between these parts and the separate set of them. The consumer lives far from this reality and does not know of this difference. The character of the work is therefore descriptive and informative. The essay uses primary data with descriptive statistics and a convenience sample, thus not probabilistic. The results ensured a higher price for the first cuts a nd greater variation. Results explained throughout the text, as mention of back and front cuts.